The training octagon: Training the anterior and posterior serape. - Santana, J. C.; Brown, L. E.; Ferrigno, V. A. (Strength and Conditioning Journal, 2016)
The purpose of this article is to explain how the anterior and posterior serape (aps) can be systematically trained using a simple movement model; the training octagon (to). The directions of the muscles are associated with the directions of the to, and a system of five basic cable/band exercises is provided for training. Tables and figures organizing and classifying the muscles, movements, and exercises further associate the training and biomechanical models of the aps. The model presented in this article is a tool for strength and conditioning professionals to use when training the core musculature.